Reform and Innovation in Islamic Boarding School Education Management: Standardization of Madrasah Diniyah Salafiyah - Hamdanah, Hamdanah (JURNAL AL-TANZIM, 2024)
This research focuses on analyzing and understanding the process of reform and innovation in the management of Islamic boarding school education, emphasizing the standardization of Madrasah Diniyah Salafiyah. This study aims to identify challenges, strategies, and impacts of reform and innovation in the context of Islamic boarding school education management by examining the implementation of standardization of Madrasah Diniyah Salafiyah. This research method uses a qualitative approach with a case study in the Madrasah Diniyah Salafiyah Islamic Boarding School. Data were collected through participatory observation, interviews with teachers and students, and analysis of curriculum and learning achievement documents. The analysis used descriptive and thematic approaches to identify patterns in implementing curriculum innovations and their impact on student achievement. The results showed that curriculum innovation has positively improved student achievement and skills. However, several challenges still need to be addressed, such as gaps in the understanding of teachers and students regarding these innovations. The implications of this research highlight the importance of continuity of education reform and management innovation in increasing pesantren's relevance, effectiveness, and competitiveness in producing qualified graduates who can compete in the global era.